ANALYSIS OF THE ROLE OF BPK IN PREVENTING AND ERADICATING CORRUPTION (A STUDY IN 4 DISTRICTS IN SOUTH SULAWESI PROVINCE - Junaidi Junaidi (Asia Pacific Fraud Journal, 2016)
The objective of this study is to test the ability of BPK (the Audit Board of the Republic of Indonesia) in preventing and eradicating corruption in regional government (district). In this study, the examination is focused on the factors that affect the treasurers to commit fraud, especially in the financial management and financial transaction area, based on the fraud triangle theory. This study is based on the interviews with 87 treasurers and former treasures period 2008-2012. The result of this study indicates that pressure and rationalization have a positive relationship with fraud. The result provides partial support for the fraud triangle theory in explaining the phenomenon of fraud. The role of BPK is as a strategic government auditor in preventing and combating corruption in regional government.